Analysis of Phase Structure Realization in Classroom Discourse: A Study of Systemic Functional Linguistics - Suparman Suparman; Charmilasari Charmilasari (Ethical Lingua: Journal of Language Teaching and Literature, 2017)
This study aims at describing the phase structure of classroom discourse in SMAN 1 Palopo. The research design employed is a qualitative study. The research location was SMAN 1 Palopo in which the population of the current study was classroom discourse in class X; while the sample were clauses that indicate the phase and interpersonal meaning of the teacher and the students who were selected using the purposive sampling technique. The source of data were the discourses in the biology, Physics and civic education classes. This study uses the theory of systemic functional linguistics to identify the clause phase structure consisting of phases and each sub-phase consists of 5 phases. Phase is used to transfer the science that aims to guide students to understand the material. Sub-phase comprises 33 phases which were divided into 4 static sub-phases and 29 dynamic sub-phases. System dominant mode shows the role of teachers in transferring science or knowledge expect information provided will be accepted by the students.